The preliminary results of earthquake observation by deployment of the local seismic network Guralp-6TD in the region of Thanh Hoa province - Toàn, Đinh Văn; Chen, Chau -Huei; Wen, Strong; Phòng, Lại Hợp; Vũ, Trần Anh; Quang, Nguyễn Thị Hồng; Ninh, Dương Thi (Vietnam Journal of Earth Sciences, 2013)
Ma River and Son La - Bim Son active faults predicted as the strongest seismogenic zones in Vietnam with the maximum earthquake can be reached 7.1 degree on Richter scale. The seismicity of these fault zones at several segments in Northwest regions is much more active than that at the southeast segments of the Thanh Hoa province. The low seismicity in these segments may be related to the sparse network of the instruments in these areas. A large region of Thanh Hoa and Nghe An provinces is distributed only three instruments, thus it is very difficult for us to sufficiently record small earthquakes. Since November 2009, in the framework of the cooperation between the Institute of Geological Sciences - VAST and the Chung Cheng National University - Taiwan, we connected a local seismic network Guralp-6TD with 12 instruments along the south-eastern of Ma River fault in Thanh Hoa Province to study more detail the seismic activity of the Ma River and Son La - Bim Son Faults. Our equipment recorded about 300 earthquakes during the past three years, and located near 190 earthquakes among them, the greatest part of them is small earthquakes. According to the study the segments of Ma River and Son La - Bim Son faults in Thanh Hoa province are not quite by seismic activity. The correlation to the tectonic fault distribution is revealed the small earthquakes happened in all the branches of the Ma River fault and the density of the earthquakes in the southwest branches is higher than in the northeast ones. The high density of the small earthquakes is detected in the section from Thuong Xuan district to the sea bank, where accepted as a stable section in the previous studies. A not small portion of the earthquakes is occured in the Son La - Bim Son, Hieu River faults, etc... Much more interesting result is the detection of a large number of small earthquakes inside the young submeridian tectonic faults Thuong Xuan - Ba Thuoc and Thach Thanh - Nong Cong. These faults are sill not well studied up to now by both tectonics and earthquake observation.